CHILDREN AND FAMILIES IN TRANSNATIONAL MIGRATION: LATIN AMERICAN AND CARIBBEAN PERSPECTIVES - Piego, Deborah; Henrique, Maria Sonia; Abramowicz, Anete (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
The objective of this article is to analyze the migration of transnational children and families in the Latin American and Caribbean context. For this purpose, we collected demographic data from CEPAL² between 2010 and 2020, and articles from authors who research the subject. We verified that transnational migrations influence and impact family dynamics and children’s subjective experiences. Age and gender issues appear in the increasing role of women, seeking better living conditions for their children, and in grandmothers who take care of grandchildren in the country of origin while women work in the destination country. The children who drive adult decision-making are agents in this process and in the destination country but participate little in the decision to migrate. Drawing from the Sociology of Childhood, we highlight that the place of migrant children is constructed from their experiences marked by social markers: race, class, gender, and country of origin. Accompanying their families on the journey, staying in the country of origin, or even being born in the destination country, children’s experiences are crossed by adult migration, non-belonging, discrimination, racism, and xenophobia. It is noteworthy that migrations mark families even when some of them remain in the country of origin.